Development of lifestyle assessment: A Delphi survey of multi-faceted health experts. - Ah-Ram Kim; Young-Myoung Lim; Ji-Hyuk Park (PLoS ONE)
Objective In the field of health promotion, there's a growing focus on adopting an academic approach to assess and evaluate the intricate and ever-evolving nature of lifestyles. This approach is crucial for shaping and improving a healthy way of life. Systematic measurement of lifestyles is essential for enhancing overall health and well-being, encompassing physical, mental, and social dimensions. This study's goal is to create an assessment tool that measures the diversity and intensity of lifestyle behaviors linked to human health. Our efforts involved developing quantitative measurement items that encompass the holistic concepts of health and lifestyle and validating them. Methods Between March and April 2023, we gathered insights from 14 experts in lifestyle and health. Building on previous research, we conducted a Delphi survey twice. In the initial survey, we collected expert opinions through open and closed-ended questions about lifestyle evaluation items. After the first survey, we corrected several items that didn't meet the Content Validity Ratio (CVR) standard before proceeding. We presented the first survey's findings to an expert panel, leading to a consensus. Results The initial Delphi round produced 76 items, and the second round resulted in 72 items after adjusting those with CVR scores of 0.51 or less. The final Content Validity Ratio was 0.83, signifying a robust validation process, with a convergence of 0.50 and a consensus level of 0.75. Conclusion In summary, this study successfully developed a comprehensive lifestyle assessment tool using a modified Delphi technique. The 72 items are categorized into eight subcategories and four overarching themes. This tool provides a systematic approach to evaluate lifestyles, promoting health and well-being across physical, mental, and social dimensions. It also assists in identifying specific lifestyle elements that require more in-depth intervention strategies, all while preserving the academic integrity of the content.